The Russia-Ukraine War and its Origins: From the Maidan to the Ukraine War - Katchanovski, Ivan (Rethinking Political Violence; Political Science and International Studies; Political Science and International Studies (R0), 2026)
This open access book examines the Russia-Ukraine war and its origins. Based on analysis of a large number of primary and secondary sources, it provides a systematic analysis of this crucial war, its nature, outcome, possibility of peaceful settlement, violence against civilians, and origins. The book examines the role of such factors as the NATO accession of Ukraine, Russian imperialism, democracy, genocide, and the far-right in the start of the war and traces the conflict escalation ladder, which culminated in this war, to preceding violent conflicts in Ukraine, in particular, the Euromaidan, the Maidan massacre, the Russian annexation of Crimea, and the war in Donbas. The Russia-Ukraine war is the most significant armed conflict of the 21st century in the entire world and in Europe since World War Two in terms of countries involved, casualties inflicted, and actual and potential impact in the world. This book analyzes the involvement of different conflict parties, such as the Ukrainian, Russian, and Western governments, Donbas separatists, and the far right, in this crucial war and in the Euromaidan, the Maidan massacre, the Russian annexation of Crimea, and the war in Donbas, and the nature of these conflicts. This book also examines support for pro-Western/pro-nationalist and pro-Russian/pro-communist political parties and presidential candidates and attitudes towards separatism and joining the European Union, NATO, and the union with Russia in regions of Ukraine in parliamentary and presidential elections and surveys since the Euromaidan.